Correction: Bayesian regression explains how human participants handle parameter uncertainty. - Jannes Jegminat; Maya A Jastrzębowska; Matthew V Pachai; Michael H Herzog; Jean-Pascal Pfister (PLoS Computational Biology)
[This corrects the article DOI: 10.1371/journal.pcbi.1007886.].